Open-mindedness in Three Dimensions - Higgins, Chris (Paideusis, 2009)
In this programmatic essay, I approach the question "What is open-mindedness?" through three more specific questions, each designed to foreground a distinct dimension along which the analysis of open-mindedness might proceed: When is open-mindedness? What is not open-mindedness? and, Where is open-mindedness? The first question refers to the temporal dimension of open-mindedness, which I analyze in terms of Dewey’s distinction between recognition and perception and the psychoanalytic concept of disavowal. The second question refers to the dialectical dimension of open-mindedness, to what the many aspects of closed-mindedness reveal about open-mindedness. Here I recall Aristotle’s doctrine of the mean. The third question refers to the dimension of scale, asking what open- and closed-mindedness look like on the interpersonal and social levels. To bring out this third dimension, I draw on Jonathan Lear's reading of the Republic and psychoanalytic group dynamics theory. Through these three related inquiries I show the range of this central intellectual virtue and bring out its connections to two central, related features of the moral life: the need for integration and the need for openness to newness and complexity.